Spatio-temporal clustering analysis of mumps in Wenzhou City from 2010 to 2023 - LI Ling, WEI Jingjiao, PAN Qiongjiao, LI Wancang, WANG Jian (预防医学)
Objective: To identify the spatio-temporal clustering analysis of mumps in Wenzhou City, Zhejiang Province from 2010 to 2023, so as to provide the basis for improving mumps prevention and control strategies. Methods: Data of mumps cases in Wenzhou City from 2010 to 2023 were collected from the Monitoring and Reporting Management System of Chinese Disease Prevention and Control Information System. The spatio-temporal clustering characteristics of mumps incidence were identified using spatial autocorrelation analysis and spatio-temporal scan analysis. Results: A total of 20 455 mumps cases were reported in Wenzhou City from 2010 to 2023, with an average annual incidence of 17.54/105. There were 12 919 male and 7 536 female cases, with a male-to-female ratio of 1.71∶1. The children aged 5-<10 years had the highest incidence of mumps at 135.29/105. The incidence of mumps showed a downward trend from 46.82/105 in 2010 to 3.59/105 in 2023 (P<0.05). The incidence of mumps peaked from May to July and from November to January during 2010 and 2012, the winter peak became less evident after 2013, and no seasonal trends were observed after 2020. Spatial autocorrelation analysis showed there was a positive spatial correlation of mumps of other years, with the exception of 2018 (all Moran's I >0, all P<0.05). Lucheng District, Longwan District, Ouhai District, Cangnan County and Rui'an City were high-high clustering sites. Spatio-temporal scan analysis showed that the primary clustering area was centered in Nanbaixiang Street, Ouhai District, covering 50 towns (streets), with the clustering time from April 2010 to August 2013; the secondary clustering area was centered in Zaoxi Town, Cangnan County, covering 24 towns (streets), with the clustering time from January 2010 to June 2013. Conclusions: The incidence of mumps in Wenzhou City from 2010 to 2023 showed a downward trend. The urban areas, Cangnan County and Rui'an City were the clustering areas.